2022
DOI: 10.1002/adma.202108818
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Polymer–DNA Gels Showing Highly Predictable and Tunable Mechanical Responses

Abstract: Dynamically crosslinked gels are appealing materials for applications that require timedependent mechanical responses. DNA duplexes are ideal crosslinkers for building such gels because of their excellent sequence addressability and flexible tunability in bond energy.However, the mechanical responses of most DNA gels are complicated and unpredictable despite the high potential of DNA. Here, we demonstrate a DNA gel with a highly homogeneous gel network and well-predictable mechanical behaviors by using a pair … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…This work aims to provide a theoretical basis for the prediction of network percolation and rheology in metallo-supramolecular polymer networks including complexes with various coordination geometries. This issue becomes relevant in many of the applications of transient hydrogels, specifically the ones that require a temporal hierarchy of relaxation modes. ,, The theoretical basis includes an extended Miller–Macosko’s model that correlates the network composition to the connectivity and a thermodynamic model that predicts the complex composition in the two-metal ion transient network, as described in Section and illustrated in Figure b. To challenge this model with experiments, where the coordination geometry and, therefore, the complex composition change effectively, we form model-type networks based on the coordination of tetraEPh polymer precursors with a mixture of divalent transition metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…This work aims to provide a theoretical basis for the prediction of network percolation and rheology in metallo-supramolecular polymer networks including complexes with various coordination geometries. This issue becomes relevant in many of the applications of transient hydrogels, specifically the ones that require a temporal hierarchy of relaxation modes. ,, The theoretical basis includes an extended Miller–Macosko’s model that correlates the network composition to the connectivity and a thermodynamic model that predicts the complex composition in the two-metal ion transient network, as described in Section and illustrated in Figure b. To challenge this model with experiments, where the coordination geometry and, therefore, the complex composition change effectively, we form model-type networks based on the coordination of tetraEPh polymer precursors with a mixture of divalent transition metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a DNA-crosslinked hydrogel had been shown to exhibit temperature-dependent stress-relaxation. In cell culture, however, temperature cannot be altered at will, and the effects of chemical matrix modifications on cell development can be difficult to disentangle from pure stress relaxation effects 61 . With the help of SRCs, for the first time the stress relaxation of a material can be adjusted systematically over 3 orders of magnitude by altering merely a few nucleobases on the DNA crosslinker sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated control over stress relaxation via chemical modifications to the polymer scaffold or side groups 26,[62][63][64][65][66] . Moreover, a DNA-crosslinked hydrogel had been shown to exhibit temperature-dependent stress-relaxation 67 . In cell culture, however, temperature cannot be altered at will, and the effects of chemical matrix modifications on cell development can be difficult to disentangle from pure stress relaxation effects.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the majority of reversible covalent bonds, whose stability can be adjusted using external catalysts or stimuli. , A prime example is the hydrazone bond formed between aldehyde and hydrazine groups, whose dissociation rate can be tuned over two orders of magnitude using aniline as the catalyst . In the same way, the dissociation of boronic ester bonds formed between boronic acid and diols strongly depends on and can be tuned by pH and temperature. Alternately, leveraging the combination of hydrophobic and electrostatic interactions, polymer precursors functionalized with heterocomplementary macrocycles and various guests are reported to form transient hydrogels with a stability that is tunable in more than five orders of magnitude. , Similarly, heterocomplementary hydrogen bonding groups are used to suppress the macroscopic phase separation between immiscible polymer precursors, but their utility in hydrogel formation is normally limited due to the competition with water. , In contrast, Sakai and co-workers have recently formed transient hydrogels using tetraPEG precursors grafted with DNA sequences, which form heterocomplementary duplexes mediated through hydrogen bonds . The stability of hydrogels could be continuously tuned by varying the composition and length of DNA segments.…”
Section: Introductionmentioning
confidence: 99%